CHARACTERISTICS OF NANOMETRIC PARTICLES OF METAL OXIDES - Rebriy, Julia; Sukhodub, Leonid; Kasianchuk, Victoria (Eastern Ukrainian Medical Journal, 2023)
Introduction. This mini-review examines the mechanisms of damage to bacterial biofilms (BB) by particles of metals (Au, Ag, Fe, Cu, Zn, Mg) and their oxides (AuО, SiO, Fe2О3, Ag2O, CuO, TiO2, ZnO, and MgO). Emphasis is placed on the mechanism which includes the formation of reactive oxygen species that affect the redox state of the bacterial cell and, as a result, its death. The mechanism of the antibacterial action of particles, ZnO, as well as their effect on the porosity and degree of swelling of the apatite-biopolymer composite, were considered in more detail. Due to the emergence of antibiotic resistance of bacterial biofilms, it has become increasingly difficult to treat them effectively. Materials and Methods. An analytical review of scientific publications was conducted using official databases. The scientific research method was employed to achieve the objective. Results. The study showed that nanoparticles of metal oxides could have a detrimental effect on bacterial biofilms using various mechanisms of antibacterial action, including oxidative stress, biofilm inhibition, inhibition of protein synthesis and DNA damage, damage to metabolic pathways, penetration through the cell membrane, and interaction with the cell wall and membrane. Conclusion. To further utilize nanoparticles of metal oxides (copper, gold, silver, titanium, and iron), the primary mechanisms of their influence on the structure of bacterial biofilms (BBs) were studied based on papers published in the world’s scientific literature. NPs have different classifications and differ in chemical composition and physical parameters, such as nanosize and surface-to-volume ratio.